Trace Fossils Of The Selorejo Formation, Rembang Zone, North East Java Basin, Indonesia - Siti Umiyatun Choiriah; Yody Rizkianto; Achmad Subandrio; Intan Paramita Haty; Desi Kumala Isnani; Nanda Ajeng Nurwantari; Muhammad Ardiyan Syah Darmawa; Hendry Wirandoko (UIR PRESS, 2023)
The Rembang Zone of the North East Java Basin is a zone that develops as a petroleum system and is one of the areas with Indonesia’s largest oil reserves. One of the lithologies in the Rembang Zone is a sedimentary rock carbonated as a marker of marine sediments. The outcrop is continuous and rich in trace fossils, especially in the Ledok and Selorejo Formations. The existence of trace fossil outcrops is crucial for the learning process of earth science, biology, and other sciences, but recently these outcrops have been closed and have become damaged. Their numbers are decreasing due to community mining activities, so unique research on trace fossils in the Rembang Zone must be done immediately. This research aims to discover the variation of trace fossils found in the Selorejo Formation. The methods used are field mapping, measured stratigraphic measurements, rock sampling, and laboratory analysis (sedimentology, petrography, and paleontology). The research shows trace fossils in Planolites, Helminthopsis, Thalassinoides, Conichnus, Chondrites, Macaronichnus, Bergauria, Ophiomorpha, Skolithos, Terebellina, Palaeophycus, and Asterosoma.